A review on the impact of anthropogenic noise on birds - Emily A. Gilbert; Jephte Sompud; Cynthia B. Sompud (Universiti Malaysia Sabah, 2017)
This review addresses the impacts of noise, the vital role of acoustic communication and the response of birds in overcoming the increased anthropogenic noise. The rapid development in human activities nowadays induce the noise that interrupt the acoustic communication of birds. Disturbance of the signal’s transmission causes detrimental impact on the birds as they are highly depending on the acoustic communication for their survival, territory defense and reproduction. Continuous exposure of the noise then results in the declination of species richness of which have been stated by several past studies. Although most of the studies stated that the negative impact as a consequence from the anthropogenic noise, however there is positive effect contributed by the noise of which are also recorded in other studies. Moreover, the impacts of other variables such as vegetation density that cause major changes to the bird population as compared to noise have also been highlighted in several studies. This indicates that several influencing factors are important in measuring impact that lead to the changes which occur within the bird population. Thus, in depth studies on the impacts of anthropogenic noise towards the species of birds by taking into account other contributing variables are important to enable that noise management to be conducted effectively especially in developing areas as a way in conserving the biodiversity of the bird population.